2012
DOI: 10.1007/978-94-007-4584-1_25
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Intermittent Hypoxia Induces Persistent Alteration of Baroreflex in Adult Male Rats

Abstract: Baroreflex is involved in the regulation of arterial blood pressure (BP). An increase in BP activates vagal inhibitory pathways to decrease heart rate; a concomitant decrease in sympathetic discharge reduces vascular resistance. Both responses reduce BP towards normal value. Conversely, a decrease in BP produces opposite effects to increase heart rate and vascular resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…Although the effect of neonatal IH on baroreflex responses during adulthood were anticipated, those on systemic blood pressure were not. Indeed, we and subsequently others have previously shown that postnatal IH exposures promote lifelong alteration in baroreflexes and in sympathetic outflow in rats (16,19,25). The present study further expands these findings to a murine animal model, but suggests that the latter species may be less likely to compensate for the deregulation of this important homeostatic blood pressure system as evidenced by the elevation of systemic systolic blood pressures, which were absent in the rat model (19).…”
Section: Discussionsupporting
confidence: 69%
“…Although the effect of neonatal IH on baroreflex responses during adulthood were anticipated, those on systemic blood pressure were not. Indeed, we and subsequently others have previously shown that postnatal IH exposures promote lifelong alteration in baroreflexes and in sympathetic outflow in rats (16,19,25). The present study further expands these findings to a murine animal model, but suggests that the latter species may be less likely to compensate for the deregulation of this important homeostatic blood pressure system as evidenced by the elevation of systemic systolic blood pressures, which were absent in the rat model (19).…”
Section: Discussionsupporting
confidence: 69%
“…However, the mechanisms underlying the diverse effects of hypobaric and normobaric hypoxia on ABP are not unclear. It has been shown that intermittent normobaric hypoxia impairs baroreflex function and then results in hypertension in rats (11). Neonatal intermittent normobaric hypoxia also induces a reduced baroreflex function in adult rats (4).…”
Section: Discussionmentioning
confidence: 99%